Big Data Analysys in Cyber Physical Systems - Abbasova, P.A. (Herald of Azerbaijan Engineering Academy, 2024)
Big Data is a modern analytical trend that enables decision-making based on more data than ever before. Developments in mobile computing, communications, and mass storage architectures over the past decade have given rise to Big Data, an unprecedented amount of valuable information generated in various forms at high speeds. The ability to process this large volume of data in realtime using Big Data analytics tools brings many benefits that can be used in cyber threat analysis systems. This article describes Big Data for cyber-physical systems, real-time stream processing, modeling and behavioral learning for real-time control, current solutions and anticipated problems, and provides some guidelines for troubleshooting.